International migration: an escape from social decline? (Emancipação, 2025)
This article presents data of a study about International Migrations. With the support of the cybernetic culture, the accomplished study used as tools the Orkut and the MSN sites, which allowed the approximation of resident emigrants in different countries. The results of the study show a connection in the repercussions of the globalization, particularly in relation to the structural unemployment and the loss of the purchasing power of the residents of the southern region of Rio Grande do Sul State, with the decision to emigrate.
Keywords: International migration. Globalization. Unemployment.